371 Use of Trello as a Project Management Tool for Collaborative Surgical Research and Audit. (28th February 2022) - Khoury, A.; Bucknor, A.; King, I.; Kerstein, R.; Nduka, C.
Abstract: Introduction: Managing surgical research projects alongside clinical commitments requires organisation, prioritisation, and communication. Our unit is a tertiary plastic surgery centre with a large workforce, high volume case load and abundant research opportunity. In a busy department, co-ordination and communication is imperative for timely high-quality research and audit output and maximum productivity. Tools can be used to support this output; we trialled use of Trello project management software to increase productivity in this context. Method: We set up a Trello account for our unit's plastic surgery department. All consultants and trainees have access, and each project has a timeline and standardised progress checklist to support completion of projects to a uniform high standard. Results: Our Trello for Surgical Research pilot has promoted organised collaborative working and reduced duplication and partial completion of audit and research projects within our department. It has encouraged engagement between smaller subgroups within the unit, and a platform to monitor progression through key stages of project development with oversight of an appointed Research Lead, resulting in an increase in completion of closed loop audits and research projects. Conclusions: Similar experiences have been described in mathematics and engineering research groups, and delivery of educational material for English Literature study, but we have not identified description of Trello as a tool for medical research. Use of such platforms increases productivity and likelihood of completion of projects, as well as providing a clear outline of a departments' research priorities and accessible opportunities for rotating juniors.